Prevalence, Transmission and Genetic Diversity of Pyrazinamide Resistance Among Multidrug-Resistant Mycobacterium tuberculosis Isolates in Hunan, China - Liu B; Su P; Hu P; Yan M; Li W; Yi S; Chen Z; Zhang X; Guo J; Wan X; Wang J; Gong D; et al. (Infection and Drug Resistance, 2024)
Binbin Liu,1,* Pan Su,1,* Peilei Hu,1,* Mi Yan,1 Wenbin Li,1 Songlin Yi,1 Zhenhua Chen,1 Xiaoping Zhang,1 Jingwei Guo,1 Xiaojie Wan,1 Jue Wang,1 Daofang Gong,1 Hua Bai,1 Kanglin Wan,2 Haican Liu,2 Guilian Li,2 Yunhong Tan1 1Clinical Laboratory, Hunan Chest Hospital, Changsha, People’s Republic of China; 2National Key Laboratory of Intelligent Tracking and Forecasting for Infectious Diseases, National Institute for Communicable Disease Control and Prevention, Chinese Center for Disease Control and Prevention, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yunhong Tan, Clinical Laboratory, Hunan Chest Hospital, Changsha, People’s Republic of China, Tel +86-13874947876, Email Tanyunhong@163.com Guilian Li, National Key Laboratory of Intelligent Tracking and Forecasting for Infectious Diseases, National Institute for Communicable Disease Control and Prevention, Chinese Center for Disease Control and Prevention, Beijing, People’s Republic of China, Tel +86-18519886112, Email liguilian@icdc.cnBackground: China is a country with a burden of high rates of both TB and multidrug-resistant TB (MDR-TB). However, published data on pyrazinamide (PZA) resistance are still limited in Hunan province, China. This study investigated the prevalence, transmission, and genetic diversity of PZA resistance among multidrug-resistant Mycobacterium tuberculosis isolates in Hunan province.Methods: Drug susceptibility testing (DST) with the Bactec MGIT 960 PZA kit and pyrazinamidase (PZase) testing were conducted on all 298 MDR clinical isolates. Moreover, 24-locus MIRU-VNTR and DNA sequencing of pncA, rpsA, and panD genes were conducted on 180 PZA-resistant (PZA-R) isolates.Results: The prevalence of PZA resistance among MDR-TB strains reached 60.4%. Newly diagnosed PZA-R TB patients and clustered isolates with identical pncA, rpsA, and panD mutations showed that transmission of PZA-R isolates played a significant role in the formation of PZA-R TB. Ninety-eight mutation patterns were observed in the pncA among 180 PZA-R isolates, and seventy-one (72.4%) were point mutations. Twenty-four of these mutations are new, including 2 base substitutions (V93G and T153S) and 22 nucleotide deletions or insertions. The W119C was found in PZA-S isolates, on the other hand, F94L and V155A mutations were found in both PZA resistant and susceptible isolates with positive PZase activity, indicating that they were not associated with PZA resistance. This is not entirely in line with the WHO catalogue. Ten novel rpsA mutations were found in 10 PZA-R isolates, which all combined with mutations in pncA. Thus, it is unpredictable whether these mutations in rpsA can impact PZA resistance. No panD mutation was found in all PZA-R isolates.Conclusion: DNA sequencing of pncA and PZase activity testing have great potential in predicting PZA resistance.Keywords: tuberculosis, pyrazinamide, transmission, pncA mutations, rpsA mutations, panD mutations, China